Oral Administration of the Japanese Traditional Medicine Keishibukuryogan-ka-yokuinin Decreases Reactive Oxygen Metabolites in Rat Plasma: Identification of Chemical Constituents Contributing to Antioxidant Activity - Matsubara, Yosuke (Molecules, 2017)
Insufficient detoxification and/or overproduction of reactive oxygen species (ROS) induce cellular and tissue damage, and generated reactive oxygen metabolites become exacerbating factors of dermatitis. Keishibukuryogan-ka-yokuinin (KBGY) is a traditional Japanese medicine prescribed to treat dermatitis such as acne vulgaris. Our aim was to verify the antioxidant properties of KBGY, and identify its active constituents by blood pharmacokinetic techniques. Chemical constituents were quantified in extracts of KBGY, crude components, and the plasma of rats treated with a single oral administration of KBGY. Twenty-three KBGY compounds were detected in plasma, including gallic acid, prunasin, paeoniflorin, and azelaic acid, which have been reported to be effective for inflammation. KBGY decreased level of the diacron-reactive oxygen metabolites (d-ROMs) in plasma. ROS-scavenging and lipid hydroperoxide (LPO) generation assays revealed that gallic acid, 3-O-methylgallic acid, (+)-catechin, and lariciresinol possess strong antioxidant activities. Gallic acid was active at a similar concentration to the maximum plasma concentration, therefore, our findings indicate that gallic acid is an important active constituent contributing to the antioxidant effects of KBGY. KBGY and its active constituents may improve redox imbalances induced by oxidative stress as an optional treatment for skin diseases.